STUDENTS’ INTEREST IN LEARNING ENGLISH OF ELEVENTH GRADE STUDENTS SMA NEGERI 1 SUKODADI - Ainia, Nur (Universitas Islam Lamongan, 2020)
This research aimed to know the students interest in learning English and to know the interest of male and females students in learning English. The type of this research was qualitative approaches. The subject of this study were the eleventh grade students of social 2 at SMA Negeri 1 Sukodadi Lamongan. Total students are 32 students. The techniques of collecting data are interview and questionnaire. The primary instruments of this research is interview instrument. In addition by using questionnaire sheet. The technique for analyzing Data collection techniques carried out in two ways, namely: interview and questionnaire. Data analysis technique using descriptive analysis, the researcher explains one by one of the two ways that can be done in data collection. The results of this study indicate that students have low interest in learning English, it also supported by the results of the questionnaire. Based on the results of the English teacher and students interviews also the questionnaire that showed students’ interest in learning English were very low, the feeling of pleasure and interest of students in learning English as well as too monotonous learning method became the main factors that cause students’ interest in learning English. Keywords: Learning interest, English lesson